Learning Motivation of the 2022 Cohort of Japanese Language Education Students at FKIP University of Riau in the Nihongo Chuukyuu 3 Course - Lestari, Indah; Intan Suri; Merri Silvia Basri (The Future of Education Journal, 2025)
Nihongo Chuukyuu is an intermediate-level Japanese language course aimed at developing students' abilities to understand grammar, discourse content, and expressions in Japanese. This study aims to determine the percentage of learning motivation among students in the Nihongo Chuukyuu course. The subjects of this research are students of the Japanese Language Education Program at FKIP University of Riau, Class of 2022, consisting of 36 students, with the focus on their learning motivation in the Nihongo Chuukyuu 3 course. The research instrument used was a questionnaire consisting of 20 questions based on six indicators of learning motivation, which were analyzed using descriptive quantitative data analysis techniques. The results show that the learning motivation of the Class of 2022 students in the Nihongo Chuukyuu 3 course has a percentage index of 69%. The motivation level of students in this course falls into the high motivation category. Factors influencing learning motivation include academic goals and aspirations, self-confidence and self-perception, physical condition and health, positive change experiences, teaching methods and teacher attention, rewards and social support, and a conducive learning environment.